Tracking and fixed ranking of leukocyte telomere length across the adult life course. Issue 4 (27th May 2013) - Benetos, Athanase; Kark, Jeremy D.; Susser, Ezra; Kimura, Masayuki; Sinnreich, Ronit; Chen, Wei; Steenstrup, Troels; Christensen, Kaare; Herbig, Utz; von Bornemann Hjelmborg, Jacob; Srinivasan, Sathanur R.; Berenson, Gerald S.; et al.
Summary: Short leukocyte telomere length (LTL) is associated with atherosclerosis in adults and diminished survival in the elderly. LTL dynamics are defined by LTL at birth, which is highly variable, and its age‐dependent attrition thereafter, which is rapid during the first 20 years of life. We examined whether age‐dependent LTL attrition during adulthood can substantially affect individuals' LTL ranking (e.g., longer or shorter LTL) in relation to their peers. We measured LTL in samples donated 12 years apart on average by 1156 participants in four longitudinal studies. We observed correlations of 0.91–0.96 between baseline and follow‐up LTLs. Ranking individuals by deciles revealed that 94.1% (95% confidence interval of 92.6–95.4%) showed no rank change or a 1 decile change over time. We conclude that in adults, LTL is virtually anchored to a given rank with the passage of time. Accordingly, the links of LTL with atherosclerosis and longevity appear to be established early in life. It is unlikely that lifestyle and its modification during adulthood exert a major impact on LTL ranking.